Cost-effectiveness analysis of robotic surgery in healthcare for older individuals: a systematic review based on randomized controlled trials - Yunkai Tang; Bing Dou (Frontiers in Public Health)
ObjectivesThe objective of this research is to assess the economic viability of robotic interventions in the management of healthcare for the aging demographic by conducting a Systematic Review and Meta-Analysis (SR/MA) of Randomized Controlled Trials (RCTs).MethodsWe conducted a SR/MA following the PRISMA guidelines and the Cochrane Collaboration recommendations. Studies of interest were pinpointed within various databases, encompassing PubMed, Web of Science, and the Cochrane Library, up until the cutoff date of November 2024. Inclusion criteria were based on the PICOS framework, focusing on older patients (≥60 years old), robotic or robot-assisted interventions, cost-related outcomes, and RCTs. The data were subjected to statistical evaluation via Stata 17 software, wherein mean discrepancies (MD) and standardized mean discrepancies (SMD) were computed, accompanied by 95% confidence intervals (CI) for precision. Sensitivity analyses were conducted to address heterogeneity.ResultsFive RCTs involving 666 patients were included. The findings revealed that robotic surgery incurred higher total costs compared to traditional surgical approaches (MD = 1316.38, 95% CI 10.68–2622.08; p = 0.048, I2 = 92.5%). Subgroup analysis revealed that operating room costs were notable higher for robotic surgeries (MD = 1151.14, 95% CI 824.63–1477.64; p = 0.000, I2 = 0.0%), while hospitalization costs were lower but not statistically significant. Quality-adjusted life year (QALY) gains were statistically significant for robotic surgeries (MD = 0.01, 95% CI 0.00–0.02; p = 0.010, I2 = 0.0%). Incremental cost-effectiveness analyses showed that robotic surgery achieved cost-effectiveness in some cases, with incremental costs per QALY ranging from $14,925.62 to $28,860, both below the commonly accepted threshold of $50,000.ConclusionRobotic surgery demonstrate potential cost-effectiveness in older individuals, particularly by improving QALY and reducing long-term healthcare costs. However, the high initial investment remains a significant barrier to adoption. Future research should focus on standardizing economic evaluations, exploring specific applications of robotic therapies, and addressing long-term cost and clinical outcomes to better inform healthcare policy and practice.